Pemanfaatan Teknologi Informasi Dalam Meningkatkan Kinerja Karyawan - Muhammad Hanif Alwani; Ayna Nur Rohmah; Anggit Dian Permana; Kusuma Erma Dana (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The use of information technology plays a role in shaping employee professionalism, thus impacting performance improvement. An employee can be categorized as professional if their work output meets the technical and ethical standards applicable to their profession. Therefore, professionalism is an important attribute that every individual in an organization must possess. The success of management in improving employee performance is also greatly influenced by the extent to which information technology is utilized. Information technology functions as a supporting instrument and driver for organizations in achieving institutional goals and improving employee performance. This study aims to analyze the use of information technology to improve employee performance in the digital era. The method used is a systematic literature review (SLR), an approach to identifying, assessing, and interpreting all research findings relevant to a specific research question or field of study. The research findings show that the application of digital technology can drive improvements in efficiency, productivity, and performance quality when implemented appropriately and in accordance with organizational needs. However, this success does not occur automatically; it is largely determined by system readiness, human resource competency, work environment support, and effective change management. Unpreparedness in these aspects has the potential to create obstacles in the adaptation process, ultimately negatively impacting performance. Thus, organizations need to combine the use of information technology with integrated human resource management strategies, strengthening competencies, and increasing employee participation to improve employeeiperformance. Keywords: Information Technology Utilization and EmployeeiPerformance Abstrak: Pemanfaatan teknologi informasi berperan dalam membentuk profesionalisme pegawai sehingga berdampak pada peningkatan kinerja. Seorang pegawai dapat dikategorikan sebagai profesional apabila keluaran pekerjaannya memenuhi standar teknis maupun etika yang berlaku dalam profesinya. Oleh sebab itu, profesionalisme merupakan atribut penting yang harus dimiliki oleh setiap individu dalam organisasi. Keberhasilan manajemen dalam upaya meningkatkan kinerja pegawai juga sangat dipengaruhi oleh sejauh mana teknologi informasi dimanfaatkan. Teknologi informasi berfungsi sebagai instrumen pendukung sekaligus pendorong bagi organisasi dalam mencapai tujuan kelembagaan serta meningkatkan performa pegawai. Kajian ini bertujuan untuk menganalisis pemanfaatan teknologi informasi dalam rangka meningkatkan kinerja karyawan di era digital. Metode yang digunakan adalah systematic literature review (SLR). Temuan penelitian memperlihatkan bahwa penerapan teknologi digital mampu mendorong peningkatan efisiensi, produktivitas, serta mutu kinerja apabila diimplementasikan secara tepat dan sesuai dengan kebutuhan organisasi. Meskipun demikian, keberhasilan tersebut tidak terjadi secara otomatis, melainkan sangat ditentukan oleh kesiapan sistem, kompetensi sumber daya manusia, dukungan lingkungan kerja, serta efektivitas pengelolaan perubahan. Ketidaksiapan pada aspek-aspek tersebut berpotensi menimbulkan kendala dalam proses adaptasi yang pada akhirnya memberikan dampak negatif terhadap kinerja. Dengan demikian, organisasi perlu memadukan pemanfaatan teknologi informasi dengan strategi manajemen sumber daya manusia yang terpadu, penguatan kompetensi, dan peningkatan partisipasi karyawan dapat meningkatkanakinerja karyawan. Kata Kunci: Pemanfaatan Teknologi Informasi dan Kinerjaikaryawan